Modern written Arabic : a comprehensive grammar - Badawi, El-Said M.; Carter, M. G.; Gully, Adrian (London ; New York : Routledge, 2016)
'Modern Standard Arabic is a complete reference guide to the grammar of modern written Arabic. The Grammar presents an accessible and systematic description of the language, focusing on real patterns of use in contemporary written Arabic, from street signs to literature. Examples are drawn from authentic texts, both literary and journalistic, published since 1990.This comprehensive work is an invaluable resource for intermediate and advanced students of Arabic and anyone interested in Arabic linguistics and the way modern standard Arabic works.Features include:comprehensive coverage of all parts of speechfull cross-referencingauthentic examples, given in Arabic script, transliteration and translationa detailed index'--
Includes bibliographical references (pages 854-856) and indexes.
Keywords: Arabic language -- Grammar